Traumatic pseudo-lipoma in 3-year-old child - Rathi, Nilesh V. (Medknow Publications & Media Pvt Ltd, 2012)
The buccal fat pad is relatively large and prominent in neonates, infants and young children. The main function of this fat pad is considered as a cushioning tissue and sucking pad. A minor tear of buccal mucosa and buccinator muscle can result in herniation of large volume of fat into oral cavity that is termed as “pseudolipoma.” The young children tend to be very playful while brushing their teeth. Improper brushing technique resulted in severe trauma to the buccal fat, including soft-tissue between buccinator and retromolar area. This article presents a case-report of a female child who developed traumatic pseudolipoma after faulty tooth brushing for long duration and its management along with its detail review of literature.